Pharmacokinetics, Safety, and Efficacy of Glecaprevir/Pibrentasvir in Adolescents With Chronic Hepatitis C Virus: Part 1 of the DORA Study. Issue 2 (13th August 2019) - Jonas, Maureen M.; Squires, Robert H.; Rhee, Susan M.; Lin, Chih‐Wei; Bessho, Kazuhiko; Feiterna‐Sperling, Cornelia; Hierro, Loreto; Kelly, Deirdre; Ling, Simon C.; Strokova, Tatiana; del Valle‐Segarra, Antonio; Lovell, Sandra; et al.
Abstract : The pangenotypic regimen of glecaprevir and pibrentasvir (G/P) is approved to treat adults with chronic hepatitis C virus (HCV) infection and has yielded high cure rates in adults in clinical trials. Approved treatment options for pediatrics may include ribavirin. A pangenotypic regimen for pediatric patients remains an unmet need. DORA is an ongoing phase 2/3, nonrandomized, open‐label study evaluating the pharmacokinetics (PK), safety, and efficacy of G/P in pediatric patients with chronic HCV. This analysis includes Part 1 of the study, conducted in adolescent patients 12‐17 years of age given the adult regimen of G/P (300 mg/120 mg) once daily for 8‐16 weeks according to the indication durations used in adults. Patients were either treatment naïve or experienced with interferon‐based regimens. The primary PK endpoint was steady‐state exposures for glecaprevir and pibrentasvir; the primary efficacy endpoint was sustained virologic response 12 weeks after treatment (SVR12). The secondary efficacy endpoints were on‐treatment virologic failure, relapse, and reinfection. Safety and tolerability were monitored. Part 1 enrolled 48 adolescent patients infected with genotypes 1, 2, 3, or 4, of whom 47 were administered G/P. All 47 patients (100%) achieved SVR12. No on‐treatment virologic failures or relapses occurred. PK exposures of glecaprevir and pibrentasvir were comparable to exposures in adults. No adverse events (AEs) led to treatment discontinuation, and no serious AEs occurred. Conclusion: Adolescent patients with chronic HCV infection treated with G/P achieved a comparable exposure to adults, 100% SVR12 rate, and safety profile consistent with that in adults. This pangenotypic regimen demonstrated 100% efficacy within the adolescent population in as little as 8 weeks of treatment.